Artikel Review AKTIVITAS ANTIOKSIDAN BEBERAPA OLAHAN TANAMAN UNTUK MENJADI PRODUK TEH - Onne Akbar Nur Ichsan; Marta Tika Handayani (Jurnal BETAHPA, 2022)
Tea is a beverage known to have high antioxidant content. Several processed teas from several plants in Indonesia have been investigated for their antioxidant content. This journal discusses some of the antioxidant content of various plants that are claimed to be teas that have been processed in various processing methods. The antioxidant test method chosen for the review of antioxidant testing in its preparations is the DPPH (1,1-Diphenyl-2- picrylhydrazyl) method because this method is widely used in various antioxidant studies. The teas found by the author from several literatures include Moringa leaf (Moringa oleifera), soursop leaf tea (Annona muricata), cocoa leaf tea (Theobroma cacao L), coffee leaf tea (Coffea arabica), and edible flowers such as flower tea. rosella (Hibiscus sabdariffa), butterfly pea flower (Clitoria ternatea), then green tea and black tea (Camellia sinensis) as a comparison. The results of the review showed that the highest level of antioxidant activity was found in moringa leaf tea (74.9% inhibition) and the lowest was found in cocoa leaves (20.31% inhibition). All samples were still under the antioxidant activity of green tea (Camellia sinensis).